Spread of multiple SARS‐CoV‐2 lineages April‐August 2020 anticipated the second pandemic wave in Lombardy (Italy). (25th January 2022) - Tallarita, Monica; Giardina, Federica; Novazzi, Federica; Gaiarsa, Stefano; Batisti Biffignandi, Gherard; Paolucci, Stefania; Rovida, Francesca; Piralla, Antonio; Baldanti, Fausto
Abstract: During the early phase of the pandemic (20 February–4 April 2020), we have investigated the temporal and geographical evolution of the virus in Lombardy showing the circulation of at least seven lineages distributed differently in the Region. In the present study, the molecular epidemiology of SARS‐CoV‐2 was monitored in a period between two pandemic waves in order to track the circulation of new variants (April‐August 2020). A great majority of SARS‐CoV‐2 strains (70.8%) belonged to lineages B, B.1, B.1.1 and B.1.1.1, and five strains belonging to four lineages were already reported in Italy (B.1.1.148, B.1.1.162, B.1.1.71, and B.1.425). In addition, 21 SARS‐CoV‐2 strains belonged to six lineages not previously observed in Italy were detected. No variants of concern were observed. A total of 152/1274 (11.3%) amino acid changes were observed among spike gene sequences and only 26/152 (17.1%) occurred in the receptor‐binding domain region of the spike protein. Results of this study are indicative of ongoing transmission throughout the lockdown period, rather than re‐introduction of novel lineages past lockdown. The use of molecular epidemiology in Italy should be promoted in order to provide additional understanding of the transmission of the disease and to have major effect on controlling the spread of disease.